Lithuania : Financial Sector Assessment - World Bank (Washington, DC, 2013)
A joint International Monetary Fund (IMF)-World Bank Financial Sector Assessment Program (FSAP) mission visited Lithuania during November 4-15, 2001 to undertake an assessment of the financial sector. The principal objective of the mission was to assist the authorities in identifying potential vulnerabilities in the Lithuanian financial system and obstacles to its future development. Financial activity is likely to grow markedly in years to come, but a large share of the intermediation of saving and investment will not take place locally, but will instead involve a specific pattern of domestic and cross-border financial activity. Institutions in the Lithuanian financial system comprise banks, leasing companies, insurance companies, and securities firms. The insurance sector is small but likely to develop significantly in the years ahead. The payment system handles only a limited number of transactions and has shown itself to be robust in previous periods of stress. The Lithuanian financial system is likely to undergo significant further development and change, driven mainly by stepped-up domestic financial system reform and the increasing integration among financial markets in Lithuania and other countries in Europe. Lithuania appears committed to fighting money laundering and terrorist finance. Controls on money laundering in the insurance and securities sectors fall well short of those in the banking sector.